Linguistic Personality of Modern Ukrainian Drama of Absurd Character - Корольова, Валерія Володимирівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”)
The article is concerned with analysis of linguistic personality of modern Ukrainian drama of absurd characters, determining typological characteristics of linguistic personalities of characters. Linguistic personality is generalized not as dominant, standard, average, capable of communicative failures and communication inactivity. Speech peculiarities of characters is defined in the ability of being creative. As a feature of characters’ communication caused by theater of the absurd philosophy, absence of direct verbal aggression and removal of heated conflict situations is shown.